Effects of deorbit evolution on space-based pulse laser irradiating centimeter-scale space debris in LEO. (December 2019) - Fang, Yingwu; Pan, Jun; Luo, Yijia; Li, Chunwang
Abstract: The aim of this work is to address the dynamic response rules of deorbit evolution for removing centimeter-scale dangerous space debris near the international space station (ISS) by space-based single laser station. According to the theory of orbital dynamics and laser irradiation technology, the deorbit model of space-based laser irradiating the centimeter-scale debris in low earth orbit (LEO) was established. The deorbit process of driving the centimeter-scale debris was simulated by analyzing the orbit and laser parameters in coplanar/non-coplanar conditions, and the distribution rules of irradiation distance with action time were also obtained. Furthermore, the dynamic characteristics of deorbit evolution were investigated by calculating the flight paths and orbital elements after the dangerous debris is irradiated, and the interaction mechanism between space-based nanosecond pulse laser and the dangerous debris was detailedly discussed by estimating collision risk between the dangerous debris and the ISS. The simulation results indicated that the collision risk between the dangerous debris and the ISS was successfully eliminated based on the designed removal scheme and given clearance windows. Therefore, it is highly important for exploring excellent clear method to master removal rules of centimeter-scale dangerous space debris in LEO by the space-based nanosecond pulse laser. Highlights: A deorbit model of driving debris is established to achieve effective clearance. Dynamic response characteristics are obtained to estimate collision risk. Dynamics behavior of deorbit evolution is described to master removal rules. Interaction mechanism between pulse laser and dangerous debris in LEO is revealed.